Johnwellsia, a new intertidal genus of Parastenheliidae (Copepoda, Harpacticoida) from the Taiwan Strait, China, including a review of the family and key to genera - Huys, Rony; Mu, Fanghong (Zootaxa, 2021)
A new genus of Parastenheliidae, Johnwellsia gen. nov., is proposed for its type and only species, J. bipartita sp. nov., collected from Dadeji Beach in Xiamen, Taiwan Strait, China. The intricate taxonomic history of the family is reviewed with special emphasis on its type genus Parastenhelia Thompson & Scott, 1903. It is concluded that P. hornelli Thompson & Scott, 1903 is the type of the genus and that the widely adopted previous designation of Harpacticus spinosus Fischer, 1860 as type species of Parastenhelia is invalid. The taxonomic concept of Parastenhelia is restricted to the hornelli-group which includes four valid species: P. hornelli, P. similis Thompson & Scott, 1903, P. oligochaeta Wells & Rao, 1987, and P. willemvervoorti sp. nov.                The currently accepted concept of Parastenhelia spinosa as a highly variable cosmopolitan species is rejected. The genus Microthalestris Sars, 1905 (type: Thalestris forficula Claus, 1863) is resurrected to accommodate most Parastenhelia species that were previously placed in the spinosa-group. Two species, Thalestris forficuloides Scott & Scott, 1894 and Parastenhelia antarctica Scott, 1912, are reinstated as valid members of the genus which further includes Parastenhelia gracilis Brady, 1910, Microthalestris littoralis Sars, 1911, P. costata Pallares, 1982, P. minuta Pallares, 1982, P. bulbosa Gee, 2006 and five new species: M. campbelliensis sp. nov.; M. polaris sp. nov.; M. santacruzensis sp. nov.; M. sarsi sp. nov. and M. variabilis sp. nov. Both the type species, Thalestris forficula, and Harpacticus spinosus are considered species inquirendae in Microthalestris. Three new genera are proposed to accommodate the remaining Parastenhelia species. Porirualia gen. nov. contains P. megarostrum Wells, Hicks & Coull, 1982 (type) and P. pyriformis Song, Kim & Chang, 2003, and is the sistergroup of Johnwellsia gen. nov. Parastenhelia aydini Kuru & Karaytuğ, 2015 is placed in the monotypic genus Karaytugia gen. nov. while all species with penicillate elements on the antenna and P1 are transferred to Penicillicaris gen. nov., including Thalestris pectinimana Car, 1884, which is removed from the synonyms of the Parastenhelia spinosa (Fischer, 1860) “complex”, and three new species: P. maldivensis sp. nov., P. penicillata sp. nov., and P. sewelli sp. nov.                The genus Karllangia Noodt, 1964 (type: K. arenicola Noodt, 1964) is relegated to a junior subjective synonym of Thalestrella Monard, 1935a (type: T. ornatissima Monard, 1935a). New or updated diagnoses for each genus, and differential diagnoses for species where appropriate, are provided. A key to the ten currently recognized genera in the Parastenheliidae is presented as well as keys to species for Parastenhelia, Microthalestris, Thalestrella and Penicillicaris gen. nov.